Forbush Effects Associated with Disappeared Solar Filaments - Olga Kryakunova; Botakoz Seifullina; Maria Abunina; Nataly Shlyk; Artem Abunin; Nikolay Nikolayevskiy; Irina Tsepakina (Atmosphere)
The Forbush effects (FEs) in cosmic rays associated with interplanetary disturbances caused by the disappearance of solar filaments (DSFs) outside active regions (ARs) are considered. In total, 481 FEs were detected for 1995–2023 using the database of Forbush Effects and Interplanetary Disturbances (FEID). The behavior of the cosmic ray density was calculated using the Global Survey Method (GSM). The distributions of the FE numbers depending on their duration and magnitude, as well as on the characteristics of the interplanetary and near-Earth medium, were obtained. It is found that the average duration of such FEs (33.4 ± 0.5 h) is almost the same as for events associated with CMEs from ARs, but the average magnitude is much smaller (0.83 ± 0.03%). It is also shown that coronal mass ejections (CMEs) caused by DSFs are often low-speed interplanetary disturbances (with an average maximum SW speed of 423.2 ± 3.5 km/s), the velocities of which are close to the speed of the background solar wind (SW). During FEs associated with CMEs after DSFs outside ARs, on average, unsettled geomagnetic activity is observed. Magnetic storms were recorded only in 19% of events. Lower values of FE magnitude and geomagnetic activity are associated with weakened magnetic fields and low speeds of such interplanetary disturbances.